Ghosts, Holes and Hybrid Spaces Imagining Sámi-Owned Futures Through Sámi Creative Practices - Marzano, Alessia (2023)
Identifying colonialism as the “dispossessor of Sámi futures,” the research on which this paper draws investigates the role of Sámi creative expressions in decolonizing/ indigenizing Sápmi and imagining possible futures through a decolonial framework encompassing decolonizing methodologies and critical arts-based research. The artistic practices of Sámi artists Elina Waage Mikalsen and Joar Nango were discussed through in-depth conversations held with them and in light of decolonizing theories seeking to de-link artistic expressions from the “colonizing gaze of authenticity” fostered by Western modernity and coloniality. Furthermore, the paper argues for considering decolonization and indigenization as complex and interlaced processes, part of a global-local spectrum. While Sámi creative expressions are political in a transformative and healing way, they can foster the creation of Sámi-owned spaces, where to discuss both local and cosmopolitical concerns while considering Sámi sovereignty as the right to pursue Sámi’s self-determined futures. publishedVersion